2017
DOI: 10.29312/remexca.v7i2.358
|View full text |Cite
|
Sign up to set email alerts
|

Relación del número de individuos de Brevicoryne brassicae con la temperatura y con su parasitoide Diaretiella rapae en brócoli en el Bajío, México

Abstract: Relación del número de individuos de Brevicoryne brassicae con la temperatura y con su parasitoide Diaretiella rapae en brócoli en el Bajío, México* Relation the number of individuals with Brevicoryne brassicae temperature and his parasitoid Diaretiella rapae in broccoli of Bajío, Mexico

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…The identified parasitoid species emerged from aphids were: Aphidius spp, Diaretiella rapae MacIntoch, and Lysiphleblus spp (Figure 1). The aphids Brevicoryne brassicae (L.) and Myzus persicae (Sulzer) were preferentially parasitized by D. rapae in 60.8 and 73% respectively in broccoli; in this regard Salas-Araiza et al 5 indicated that the parasitism of D. rapae in B. brassicae reached up to 35.7% in January, but they did not report the presence of parasitism in M. persicae; D. rapae is a specialist parasitoid of B. brassicae and presents a high degree of specificity for the host and its habitat, it uses the smell of the plant to locate the host, but Aphidius nigripes Ashmead is a polyphagous parasitoid that does not present a response, the smell of the plant. 6 The green grass aphid Schizaphis graminum (Rondani) was parasitized by Aphidius spp up to 48%, Salas-Araiza et al 7 pointed out the potential of Aphidius spp as a parasitoid of aphids; observed that the yellow sugarcane aphid Melanaphis sacchari (Zehntner) was parasitized by Aphidius spp in 31% and Praon in 29%.…”
Section: Resultsmentioning
confidence: 95%
“…The identified parasitoid species emerged from aphids were: Aphidius spp, Diaretiella rapae MacIntoch, and Lysiphleblus spp (Figure 1). The aphids Brevicoryne brassicae (L.) and Myzus persicae (Sulzer) were preferentially parasitized by D. rapae in 60.8 and 73% respectively in broccoli; in this regard Salas-Araiza et al 5 indicated that the parasitism of D. rapae in B. brassicae reached up to 35.7% in January, but they did not report the presence of parasitism in M. persicae; D. rapae is a specialist parasitoid of B. brassicae and presents a high degree of specificity for the host and its habitat, it uses the smell of the plant to locate the host, but Aphidius nigripes Ashmead is a polyphagous parasitoid that does not present a response, the smell of the plant. 6 The green grass aphid Schizaphis graminum (Rondani) was parasitized by Aphidius spp up to 48%, Salas-Araiza et al 7 pointed out the potential of Aphidius spp as a parasitoid of aphids; observed that the yellow sugarcane aphid Melanaphis sacchari (Zehntner) was parasitized by Aphidius spp in 31% and Praon in 29%.…”
Section: Resultsmentioning
confidence: 95%
“…A positive correlation was also demonstrated between the average number of B. brassicae on broccoli (Brassica oleracea var. itálica) and the percentage of D. rapae parasitism in Mexico (Salas-Araiza et al, 2016). However, parasitoid density may present a delay in response to host density (Begon, Townsend &.…”
Section: Parasitism and Parasitoidsmentioning
confidence: 99%
“…Genera of Aphidiidae (Hymenoptera) parasitized aphids at Bajío Guanajuatense (Salas-Araiza et al 2017). Salas-Araiza et al (2016) mentioned cruciferous plants were infested by cabbage aphid, Brevicoryne brassicae L., causing crop damage and contamination especially during harvest. Natural enemies of aphids were studied in the State of Guanajuato.…”
Section: Introductionmentioning
confidence: 99%
“…Number of Aphids per Species at Irapuato, Guanajuato, Mexico It is one of the main species of sucking insects of vegetables at Bajío Guanajuatense, with consequent damage by infecting them with viruses. Cabbage aphid, Brevicoryne brassicae (L.), is a monophagous species associated with cultivated and wild cruciferous plants, the main damage is contamination of the product at harvest because no insects per plant are economically permitted(Salas-Araiza et al 2016). …”
mentioning
confidence: 99%